Evaluation of Beneficial Effects of Melilotus officinalis on Blood Profiles in iron Overloaded Sprague Dawley Rats - Sheikh, N.A.; Kosalge, S.B.; Desai, T.R.; Dewani, A.P.; Mohale, D.S.; Tripathi, A.S. (Journal of Hematology Research, 2020)
Present study deals with the investigation of beneficial effects of different fraction of Melilotus officinalis (M. officinalis) on the toxic effects of iron on different blood parameters in iron overloaded sprague dawley rats. The six IP injections of iron dextran (12.5 mg/100g) were administered uniformly over a period of 30 days to induce iron overload. Different fractions of M. officinalis were given orally and Deferoxamine (DFO) subcutaneously for 30 days. The blood parameters were estimated on 15th and 30th day of treatment. Rats exposed to iron showed significant (p < 0.01) decrease in RBC counts, Total and Differential WBC counts and Platelet counts. This indicates that excess of iron in iron overloaded disease can leads to bone marrow suppression. The animals treated with methanolic fraction of methanolic extract (MFME) and methanolic fraction of aqueous extract (MFAE) of M. officinalis shows significant (P<0.01) improvement in haematological parameters as compared to disease control (DC) rats. Greater beneficial effects were observed on 30th day and at higher dose (300 mg/kg) as compared to 15th day and at lower dose (150 mg/kg). These results suggested that M. officinalis have beneficial effects on blood parameters in iron intoxicated rats.